PREVALENCE OF COCCIDIOSIS AND CECAL COCCIDIOSIS AMONG BROILER FARMS IN DUHOK PROVINCE, IRAQ - Shameeran Ismael; Khalid Aziz; Farhad Mikaeel (Basrah Journal of Veterinary Research)
This study aimed to determine the prevalence of coccidiosis in broiler farms in Duhok Province, Iraq. A cross-sectional study was performed from June to October 2023. 600 fresh fecal samples were collected from the litters of the suspected farms, and the parasitological examinations were carried out using standard methods by using both direct fecal and flotation fecal methods for searching for coccidian oocysts. Also, 600 intestine and ceca samples were collected from the same chicken for macroscopic examination to report the presence of any pathological changes in the intestine and the ceca. The study findings revealed a high prevalence rate of coccidiosis (60%) among broiler farms in Duhok Province. Regarding ages, the ages 4-6 weeks were observed the most prevalent for infection (66.56%) than in other age groups. This study revealed that the infection rate of coccidiosis was higher in the Autumn season than in the summer season. According to the gross examination, most cases showed positive for Eimeria tenella (4433%), which indicates cecal coccidiosis and (55.7%) were positive with other Eimeria spp. Finally, some positive cases of Eimeria tenella were found infected with other species. The prevalence of coccidiosis among broiler farms was high in this study, especially, cecal coccidiosis and this is associated with several risk factors such as poor management, bad ventilation systems, humidity, and inadequate biosecurity systems in the farms.